A new species of bonefish, Albula koreana (Albuliformes: Albulidae) from Korea and Taiwan - Kwun, Hyuck Joon; Kim, Jin Koo (Zootaxa, 2011)
A new species of the genus Albula of the family Albulidae is described based on five specimens collected from Korea and Taiwan. Its new scientific name, Albula koreana sp. nov., is derived from its type locality (Korea). We compared Albula koreana sp. nov. with its similar species, A. argentea from Fiji (seven specimens), using morphological and molecular methods. Albula koreana sp. nov. differs morphologically from A. argentea in its tooth patch distributions on the mesopterygoids and parasphenoid. The tooth patches on the mesopterygoids are distributed more anteriorly than those on the parasphenoid in Albula koreana sp. nov. On the other hand, the anterior end of the tooth patches on the mesopterygoids almost corresponds to that of the tooth patches on the parasphenoid in A. argentea. The numbers of vertebrae also differ between the two species (77–78 in Albula koreana sp. nov. vs 72–73 in A. argentea). We analyzed 546 base pairs of the mitochondrial cytochrome b gene sequence, and the Albula koreana sp. nov. sequence differed considerably from that of A. argentea. Kimura’s genetic distances between them were very large (15.9%–16.4%), robustly supporting the new species Albula koreana sp. nov.